2018
DOI: 10.2174/1574893612666171121154017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bone Metastasis-associated Genes of Gastric Cancer by Genome-wide Transcriptional Profiling

Abstract: Background: Gastric cancer is one of the leading causes of cancer-related mortality worldwide. Genome-wide transcriptional profiling has provided valuable insights into the molecular basis underlying processes involved in gastric cancer initiation and progression. </P><P> Objective: To understand the pathological and biological mechanisms of gastric cancer metastasis in a genome-wide context. </P><P> Method: In this study, we constructed libraries from blood of gastric cancer patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Cancer is still a severe health problem globally, and lots of people have died from cancer ( Liao et al, 2018 ; Cheng et al, 2019a ; Zeng W. et al, 2019 ; Zhang Y. et al, 2019 ; Zhou et al, 2019 ; Yang et al, 2020 ). Traditional cancer treatments kill not only cancer cells but also normal cells, and the medical costs are very high ( Feng, 2019 ; Lin et al, 2019 ; Li Y.H. et al, 2020 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is still a severe health problem globally, and lots of people have died from cancer ( Liao et al, 2018 ; Cheng et al, 2019a ; Zeng W. et al, 2019 ; Zhang Y. et al, 2019 ; Zhou et al, 2019 ; Yang et al, 2020 ). Traditional cancer treatments kill not only cancer cells but also normal cells, and the medical costs are very high ( Feng, 2019 ; Lin et al, 2019 ; Li Y.H. et al, 2020 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer (GC) is a very common malignant tumor, and its prognosis is relatively poor. In 2015, it was found that the incidence rate of GC was second in all cancers ( Chen et al, 2015 ; Lin et al, 2019 ; Mottini et al, 2019 ). Due to the hidden nature of the disease, the early symptoms are not obvious.…”
Section: Introductionmentioning
confidence: 99%
“…Gene is merely a “formulation” of the cell, and the protein encoded by the gene is ultimately a functional participant in normal and cancer physiology [23] . Thus, while the genetic background contributes in part to the susceptibility and development of cancer [24] , cancer can now be considered as a proteome disease and has more links to the post-transcriptional steps [25] , [26] . In terms of patient prognosis, there is an urgent need for protein markers distinguishing cancer patients from normal individuals.…”
Section: Introductionmentioning
confidence: 99%